Classification of R Plasmids by Incompatibility in Pseudomonas aeruginosa - Sagai, H. (1976)
R plasmids identified in Pseudomonas aeruginosa strains isolated in our laboratories were classified by their incompatibility characters by using intraspecies conjugation in P. aeruginosa. The fertility factor, FP2, was compatible with R plasmids belonging to all groups, and was classified in a new group. From these data, the plasmids examined have been placed into seven or eight incompatibility groups.